Ionic Liquid Assisted Imprint for Efficient and Stable Quasi-2D Perovskite Solar Cells with Controlled Phase Distribution - Peng, Haibin; Li, Dengxue; Li, Zongcai; Xing, Zhi; Hu, Xiaotian; Hu, Ting; Chen, Yiwang (Nano-Micro Letters, 2023)
Although two-dimensional perovskite devices are highly stable, they also lead to a number of challenges. For instance, the introduction of large organic amines makes crystallization process complicated, causing problems such as generally small grain size and blocked charge transfer. In this work, imprint assisted with methylamine acetate were used to improve the morphology of the film, optimize the internal phase distribution, and enhance the charge transfer of the perovskite film. Specifically, imprint promoted the dispersion of spacer cations in the recrystallization process with the assistance of methylamine acetate, thus inhibited the formation of low-n phase induced by the aggregation of spacer cations and facilitated the formation of 3D-like phase. In this case, the corresponding quasi-2D perovskite solar cells delivered improved efficiency and exhibited superior stability. Our work provides an effective strategy to obtain uniform phase distribution for quasi-2D perovskite. Highlights: 1 The strategy of imprint assisted with methylamine acetate effectively ameliorates the morphology of the film, optimize the internal phase distribution, and enhance the charge transfer of the perovskite film. 2 The combination of imprinting with additive engineering improves the phase distribution within quasi-2D perovskite and promote the carrier transport, resulting in a power conversion efficiency of 18.96% with specific good reproducibility.